Photoactive Thin Silver Films by Atmospheric Pressure CVD - Heather M. Yates; Lucy A. Brook; David W. Sheel (International Journal of Photoenergy)
We report the visible and UV activity of thin silver films. The films are grown using a CVD process employing aqueous-based silver precursors, flame-assisted chemical vapour deposition. This approach overcomes many of the previously encountered limitations to silver deposition by employing an atmospheric pressure process, low-cost and low-toxicity precursors. The resultant films are assessed for activity using stearic acid destruction as a model compound. We also report on the addition of titania to these silver films to increase the potential functionality. This activity is also demonstrated, where the films appear largely transparent to the eye, further widening the potential application of this work. It is speculated that the nanoparticulate nature, of the CVD silver, is crucial in determining photoactivity.